Effect of electrolytic and neurotoxic lesions of the median raphe nucleus on anxiety and stress - Andrade, TGCS; Graeff, F. G. (Elsevier B.V., 2001)
To study the role played by 5-HT mechanisms of the MRN, behavioural and physiological parameters were presently measured in rats having either electrolytic or 5,7-dihydroxytryptamine (5,7-DHT) lesion of the MRN made 7 days before testing. Half the animals were submitted to 2-h restraint 24 h before the test. In the elevated plus-maze, the electrolytic lesion increased the percentage of open-arm entries and of time spent on open arms - an anxiolytic effect - in both restrained and nonrestrained rats. The neurotoxic lesion had a similar effect, but only on restrained rats. Restraint had anxiogenic effect. The electrolytic lesion increased transitions between the light and dark compartments and the time spent in the bright compartment of the light-dark box in both restrained and nonrestrained rats. The neurotoxic lesion only increased bright time in restrained rats. The incidence, number and size of gastric ulcers were increased by either the electrolytic or the neurotoxic lesion in both restrained and nonrestrained animals. Both types of lesion depleted 5-HT in the hippocampus in restrained and nonrestrained rats. Restraint increased 5-HT levels. These results implicate 5-HT mechanisms of the median raphe nucleus in the regulation of anxiety and in the genesis of gastric stress ulcers. (C) 2001 Elsevier B.V. All rights reserved.
Keywords: median raphe nucleus; 5-HT; anxiety; gastric ulcers; stress